DAMPAK BISNIS FASHION ONLINE TERHADAP TINGKAT PENDAPATAN PEDAGANG DI PASAR PETISAH MEDAN - Muhammad Yafiz,Sri Ramadhani, Wardah Nst, (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2021)
The purpose of this study was to determine the impact of the online fashion business on the income level of traders in the Medan Petisah market. The method used is a quantitative approach. The data collection instrument used primary and secondary data. The data analysis used in this research is validity test, reliability test, simple linear regression test, and determinant test using SPSS version 22.0. Online fashion business has a positive and significant impact on the income level of traders in the Medan Petisah market. This is evidenced by the value of the positive regression direction coefficient that is equal to 0.364 and significant p = 0.001 <0.05. From the determination test of R2, it is known that the percentage of the influence of the variable is 0.612 and the magnitude of the influence of the independent variable or online fashion business with the dependent variable is the income level variable called the coefficient of determination (R square) of 0.611 or 61.1%. This means that the impact of the online fashion business on the income level of traders in the Medan Petisah market is 61.1% while the remaining 38.9% is influenced by other variables.